Karakteristik Fisik dan Mekanik Papan Partikel dari Serbuk Kayu Sengon Menggunakan Perekat Sagu yang Dimodifikasi dengan Asam Sitrat dan Kitosan - Remigius Lallo; Rosalia Sira Sarungallo; Maxie Djonny (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The utilization of wood waste as a raw material for particleboard is expected to reduce industrial dependence on solid wood. In addition, the use of synthetic adhesives that potentially produce hazardous emissions has encouraged the development of natural adhesives based on sago modified with citric acid and chitosan. This study aimed to evaluate the effect of variations in citric acid and chitosan addition to sago adhesive on the physical and mechanical properties of particleboard. The research stages included the preparation of sengon wood sawdust, formulation of sago adhesive, particleboard manufacturing, and testing of the board’s physical and mechanical properties. The results of the study showed that particleboard with adhesive composition with the addition of 5%, 10%, and 15% citric acid and 5% and 10% chitosan of the weight of sago met the SNI 03-2105-2006 for density, moisture content, and internal bond strength. The addition of citric acid improved the physical properties of particleboard; however, excessive concentrations reduced the mechanical properties of the board. FTIR analysis indicated that chitosan has the potential to enhance the mechanical properties of particleboard.